Chlamydia muridarum mutant CM-pGP3S as a novel attenuated live rectal vaccine protects against genital tract infection - Jingyue Ma; Tianyuan Zhang; Qi Tian; Meng Xiao; Long Han; Quanzhong Liu; Guangming Zhong; Yuanjun Liu (Frontiers in Cellular and Infection Microbiology)
IntroductionChlamydia trachomatis (CT) is a major sexually transmitted pathogen with severe complications. Using Chlamydia muridarum (CM) as a model, this study evaluates the attenuated mutant Chlamydia muridarum (CM-pGP3S) as a novel rectal vaccine to protect against genital tract infection and pathology.MethodsFemale C57BL/6 mice were rectally immunized with low (1×103), middle (1×105), or high (1×107) doses of CM-pGP3S. Mice were challenged intravaginally with wild-type Chlamydia muridarum 63 days post-immunization. Protection was assessed via genital Chlamydia shedding, hydrosalpinx incidence (gross/histopathology), serum IgG, fecal IgA, and T cell responses. Gut microbiota stability was analyzed using qPCR.ResultsCM-pGP3S immunization significantly reduced CM-WT genital shedding duration (3–7 days vs. 21 days in controls, p < 0.01) and hydrosalpinx incidence (0% vs. 80% in controls, p < 0.01). Elevated systemic and mucosal immunity were observed, including higher serum IgG (1:100–1:1600 dilutions, p < 0.05–0.01) and fecal IgA (p < 0.05–0.01). CD4+ and CD8+ T cells exhibited increased IFN-γ (p < 0.01), while CD8+ T cells showed elevated TNF-α and IL-2 (p < 0.05). No colitis or significant gut microbiota disruption occurred post-immunization.DiscussionRectal CM-pGP3S vaccination induces robust transmucosal immunity, protecting against genital Chlamydia infection and pathology without gastrointestinal adverse effects. This highlights its potential as a safe and effective mucosal vaccine strategy to combat CT genital tract infections.